Numerical simulations of the liquid-vapor phase change dynamic processes in a flat micro heat pipe. (February 2020) - Fang, Wen-Zhen; Tang, Yu-Qing; Yang, Chun; Tao, Wen-Quan
Highlights: Dynamic behaviors of coupled flow and heat transfer in heat pipes are studied. Liquid-vapor phase change processes are simulated by lattice Boltzmann models. No any empirical models are necessary in the numerical modeling. Receding behaviors and drying out of working fluids are studied. Optimized wick structures are designed and their performances are evaluated. Abstract: The performance of a flat micro heat pipe (FMHP) is highly dependent on the wick geometry. Understanding the dynamic behaviors of liquid-vapor phase change in the FMHP is of significance for its optimal design, especially the wick geometry. In this work, a pore-scale three-dimensional pseudopotential lattice Boltzmann model coupled with a thermal model is developed to study the transient behaviors of the FMHP without any empirical equations. In the developed model, the curvature of liquid-vapor meniscus can be automatically adjusted according to the external heat source and the receding behavior of liquid films can be captured. Besides, effects of detailed wick microstructures on the performance of the FMHP are systematically studied. The results show that a more hydrophilic grooved wick yields a higher capillary force to improve the working ability. The working temperature and liquid charge amount significantly affect the performance of the FMHP. The grooved-type wick with a trapezoid shape has the best performance, next by the rectangular shape and then inversed trapezoid shape. For the micro-pillar type wick, with a relatively small pillar pitch at the evaporation section and a large pitch at the condensation section can improve the working performance.